2015
DOI: 10.1007/s10495-015-1164-7
|View full text |Cite
|
Sign up to set email alerts
|

A novel dual EGFR/HER2 inhibitor KU004 induces cell cycle arrest and apoptosis in HER2-overexpressing cancer cells

Abstract: Human epidermal growth factor receptor 2 (HER2) is a validated therapeutic target in cancer therapy, and HER2 protein-tyrosine kinase inhibitors have attracted considerable attention in the field of searching for novel anticancer drug candidates. In this study, we investigated the anticancer effect of KU004, a novel dual EGFR and HER2 inhibitor in vitro and in vivo. In vitro, KU004 preferentially inhibited the growth of HER2-overexpressing breast and gastric cell lines and HER2 expression level significantly c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
(42 reference statements)
0
6
0
Order By: Relevance
“…By comparison, antibodies can stimulate the HER2 pathway and potentially accelerate cell proliferation and tumorigenesis. 45-50 …”
Section: Discussionmentioning
confidence: 99%
“…By comparison, antibodies can stimulate the HER2 pathway and potentially accelerate cell proliferation and tumorigenesis. 45-50 …”
Section: Discussionmentioning
confidence: 99%
“…In vivo study found that KU004 reduced growth of NCI-N87 xenograft dramatically in a dose-dependent manner by inducing apoptosis. These in vivo and in vitro results indicate that KU004 has the potential to treat HER2 + BC in the future (76).…”
Section: Her2 Tk Inhibitorsmentioning
confidence: 66%
“…21 Cell cycle dysregulation is the hallmark of cancer. 22 Cell cycle arrest can lead to inhibition of cell growth. 23 Therefore, in our study, we further confirmed whether cell growth inhibition in gastric cancer cells was associated with cell cycle arrest.…”
Section: Discussionmentioning
confidence: 99%